Plant-based supplements in enhancing exercise performance and recovery - Jiao, Xianwei; Liu, Xin; Cao, Qinglei; Deng, Zhongyuan (Frontiers in Nutrition, 2025)
Plant-based supplements are redefining sports nutrition through their dual capacities to enhance exercise performance and accelerate recovery. The literature is based on a search of the Web of Science Core Collection (November 12, 2024) for studies on plant-based supplements and exercise, limited to those with clear mechanistic or clinical relevance. This review delineates the mechanistic roles of plant-derived amino acids, antioxidants, and bioactive extracts in modulating key physiological pathways underlying athletic performance and recovery. Specifically, plant protein formulations have been shown to rival their animal-derived counterparts in stimulating myofibrillar protein synthesis, a cornerstone process in muscle repair and growth. In addition, polyphenols (a major class of plant antioxidants) mitigate exercise-induced oxidative stress through two primary mechanisms: scavenging reactive oxygen species and modulating endothelial function. However, chronic high-dose antioxidant use may attenuate adaptive signaling pathways—such as mTOR or Nrf2 activation—critical for developing exercise-induced physiological adaptations. The review concludes with a discussion of precision dosing as a critical factor in balancing efficacy and safety, and it identifies areas in which further research is needed, including long-term safety data, inter-individual variability, and the development of synergistic phytochemical formulations. The review identifies the need for large-scale research clinical trials to validate causality, optimized delivery systems, and population-specific guidelines to address herb–drug interactions. Ultimately, this review calls for evidence-based research to be conducted on the relationship between botanical supplements and sports nutrition, with a particular emphasis on interdisciplinary collaboration to unlock the translational potential.